Hi, just like to check my answer with someone for the this question

calculate y"+9y=H(t-1) y(0)=0 y'(0)=-2 using laplace method

H is heaviside fuction

my solution:

y=cos(3t)-2sin(3t)/3 + H(t-1)/9(H(t-1) + cos (3t-3) )

thanks

Printable View

- October 31st 2010, 07:55 PMFibonacciLaplace Transformation
Hi, just like to check my answer with someone for the this question

calculate y"+9y=H(t-1) y(0)=0 y'(0)=-2 using laplace method

H is heaviside fuction

my solution:

y=cos(3t)-2sin(3t)/3 + H(t-1)/9(H(t-1) + cos (3t-3) )

thanks - October 31st 2010, 11:46 PMmr fantastic